A STUDY ON THE INHIBITORY EFFECT OF RADIX SEMIAQUILEGIAE EXTRACT ON HUMAN HEPATOMA HEPG-2 AND SMMC-7721 CELLS - Duan, Shu-peng; Jin, Cai-ling; Hao, Jie; Hou, Li-juan; Li, Ai-hui; Zhu, Zhi-ping; Gao, Jian-hui; Pan, Ying (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The main objective of this paper was to investigate the extraction process of ethanol extract of Radix Semiaquilegiae, as well as its inhibitory activity on human hepatoma HepG-2 and SMMC-7721 cells, and to compare the inhibitory effects of different concentrations of ethanol extracts against these two hepatoma cells. Ethanol reflux extraction and ultrasound-assisted extraction with ethanol at room temperature were used in the extraction process, and MTT assay was mainly used in the activity experiment to perform in-vitro anti HepG-2 and SMMC-7721 cell activity screening of ethanol extract, and to calculate the cell inhibition rates of the extracts. The results showed that among the two types of extracts, ethanol reflux extract had more superior antitumour activity to that of the ultrasonic extract, but all of the extracts obtained had certain anti-cancer activities, and the anti-proliferative activity increased with the increase of concentration.